Looking Beyond the Horizon : How Climate Change Impacts and Adaptation Responses Will Reshape Agriculture in Eastern Europe and Central Asia - Sutton, William R.; Srivastava, Jitendra P.; Neumann, James E. (Washington, DC: World Bank, 2013)
This volume presents a synthesis of the multi-country collaborative program of analytical and advisory activities titled reducing vulnerability to climate change in European and Central Asian (ECA) agricultural systems. Climate change and its impacts on agricultural systems and rural economies are already evident throughout the ECA region. Adaptation measures now in use in the region-largely piecemeal efforts-would be insufficient to prevent impacts on agricultural production over the coming decades. Interest is growing among governments and many of their development partners to gain a better understanding of the exposure, sensitivities, and impacts of climate change at the farm level, and to develop and prioritize adaptation measures to build resilience to the potentially adverse consequences. Agricultural production is inextricably tied to climate, making agriculture one of the most climate-sensitive of all economic sectors. In many countries, such as the four examined in this work, the risks of climate change for the agricultural sector are a particularly immediate and important problem because the majority of the rural population depends either directly or indirectly on agriculture for their livelihoods. The risks of climate change cannot be effectively dealt with and the opportunities cannot be effectively exploited without a clear plan for aligning agricultural policies with climate change, for developing key agricultural institution capabilities, and for making needed infrastructure and on-farm investments. However, an important advantage of the innovative approach developed for this assessment is that it can be applied to gauge the climate change risks and opportunities of any country's farming systems, and it can be used to define and prioritize practical adaptation options.